SINGLE JOURNAL BIBLIOMETRIC STUDIES: A REVIEW - Tiew, Wai Sin (Malaysian Journal of Library and Information Science, 1997)
Reviews 102 papers on single journal bibliometric studies covered by LISA Plus and CRLIS database during 1969 to Spring 1997.